Notas sobre cráneo, otolitos y biología de Lepidosiren paradoxa (Pisces, Dipnoi) - González Naya, María Jimena (2008)
Lungfishes are a singular group of Sarcopterygii which in the Neotropics is represented by Lepidosiren paradoxa. They present anatomical and physiological features that allow them to survive under adverse conditions. Here we described and illustrated the otoliths and determinate their composition. L. paradoxa skull is also described and illustrated with emphasis in the jaw morphology. This skull was compared with the skull of the other extant lungfishes Neoceratodus (Australian lungfish) and Protopterus (African lungfish). Experimental observations were included on the behavior in aquarium and on the construction of galleries under laboratory conditions. L. paradoxa otoliths presented subcircular shape with a convex internal face, a narrow sulcus of regular edges, marginal and parallel to the dorsal edge. The external face presented calcareous concretions and heterogeneously distributed undulations. The otholith chemical composition differs from most of marine and freshwater teleost, but resembles to other dipnoos. The skull streamlined presents numerous bones fusions in the occipital and parietal region and exhibits a significant sagital crest. The jaw suspension showed fusion of superior jaw with the skull. Both jaws have dental plates with prominent crests. The distance between the first and the second crest in the inferior jaw increases in relation to total length. Overall, skull and otolith showed great similarities with the African genus.